Human frictions in the transmission of economic policy - Francesco D'Acunto; Daniel Hoang; Maritta Paloviita; Michael Weber (Bank of Finland, 2021)
Many consumers below the top of the distribution of a representative population by cognitive abilities barely react to monetary and fiscal policies that aim to stimulate consumption and borrowing, even when they are financially unconstrained and despite substantial debt capacity. Differences in income, formal education levels, economic expectations, and a large set of registry-based demographics do not explain these facts. Heterogeneous cognitive abilities thus act as human frictions in the transmission of economic policies that operate through the household sector and might imply redistribution from low- to high-cognitiveability agents. We conclude by discussing how our findings inform the microfoundation of behavioral macroeconomic theory.
URN:NBN:fi:bof-202109091422
Keywords: D12; D84; D91; E21; E31; E32; E52; E65; 330; Cognition; Behavioral Macroeconomics; Heterogeneous Agents; Fiscal and Monetary Policy; Beliefs; Redistribution; Inequality; Survey Data; Household Finance